Weed management in pulses: Why, when and how - Kumar, Narendra; Singh, Kranti Kumar (Indian Farming, 2015)
Pulses provide not only nutritious food and feed but also improve soil health and crop productivity. India is top producer of pulses in world accounting 25% of global production. In spite of that pulse productivity in country is only 640 kg/ha, which is lower than many countries and crops. One of the major constraints is poor weed management, which causes yield loss of up to 80%. Therefore, proper weed management is must to realize yield potential of any pulse crop. Various weed management approaches can be used as discussed based on crop and their ecology, and availability to enhance pulse production in country.